Analisis Pendapatan Usahatani Cabai Di Taraitak Raya Kecamatan Langowan Utara Kabupaten Minahasa (Studi Perbandingan Antara Cabai Merah Keriting (Capsiccum Annum L.) Dan Cabai Rawit - Elsa Eman; Juliana R. Mandei; Tommy F. Lolowang (Sam Ratulangi University, 2022)
This study aims to analyze the comparison of income and the feasibility of farming curly red chili and cayenne pepper in Taraitak Raya, North Langowan District, Minahasa Regency. This research was conducted for 3 months from March 2022 to May 2022. The location of this research is in Taraitak Raya which consists of two villages namely Taraitak Village and Taraitak Satu Village, North Langowan District, Minahasa Regency. The study used of primary data obtained from direct observation and interviews with respondents based on a list of questions. Secondary data were obtained from agencies related to this research. The sampling method used the census method as many as 11 curly red chili farmers consisting of 7 farmers in a period of 11 harvests and 4 farmers had finished harvesting the whole, 12 cayenne pepper farmers consisting of 11 farmers in a period of 11 harvests and 1 farmer had finished harvesting overall, so the sample in this study amounted to 23 farmers. The analytical method used in this research is income and feasibility analysis and t-test (Independent Sample t-Test). The results showed that the average farm income of curly red chili and cayenne pepper was significantly different. The average income of curly red chili farming is greater than the average income of cayenne pepper farming. The value of R/C Ratio in curly red chili farming and cayenne pepper farming are both > 1 so that they are both feasible to be cultivated and developed. The R/C Ratio value of curly red chili farming is greater than that of cayenne pepper farming. So that curly red chili farming is more feasible to be cultivated and developed compared to cayenne pepper farming.